2013
DOI: 10.2196/jmir.2718
|View full text |Cite
|
Sign up to set email alerts
|

Activities on Facebook Reveal the Depressive State of Users

Abstract: BackgroundAs online social media have become prominent, much effort has been spent on identifying users with depressive symptoms in order to aim at early diagnosis, treatment, and even prevention by using various online social media. In this paper, we focused on Facebook to discern any correlations between the platform’s features and users’ depressive symptoms. This work may be helpful in trying to reach and detect large numbers of depressed individuals more easily.ObjectiveOur goal was to develop a Web applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 38 publications
2
79
1
3
Order By: Relevance
“…The total number of participants across all reviewed studies was 35,044. Research was identified from 14 countries including the Philippines, 20,21 Turkey, 22,23 Serbia, 24,25 Australia, 26 Greece, 27 and Korea, 28 reflecting the global nature of the phenomenon under study. Participant age ONLINE SOCIAL NETWORKING AND DEPRESSION !…”
Section: Appraisal Of Reporting Qualitymentioning
confidence: 99%
“…The total number of participants across all reviewed studies was 35,044. Research was identified from 14 countries including the Philippines, 20,21 Turkey, 22,23 Serbia, 24,25 Australia, 26 Greece, 27 and Korea, 28 reflecting the global nature of the phenomenon under study. Participant age ONLINE SOCIAL NETWORKING AND DEPRESSION !…”
Section: Appraisal Of Reporting Qualitymentioning
confidence: 99%
“…They used crowdsourcing to screen Twitter users with the CES-D test (Beekman et al, 1997), while others analyzed one year of Facebook status updates for DSM diagnostic critera of a Major Depressive Episode (Moreno et al, 2011). In addition, Park et al (2013) predicted results of the Beck Depression Inventory (Beck et al, 1961).…”
Section: Related Workmentioning
confidence: 97%
“…In fact, even Internet usage itself seems to vary as a function of being depressed (Katikalapudi et al, 2012). Other behaviors include social networking (Moreno et al, 2011) and differences in location sharing on Facebook (Park et al, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…Simple mood scales for self-assessment such as a 7-point selection from -3 till 3 have shown statistically significant correlations with clinical validated rating scales such as the HDRS [57]. For example, there is high correlation between the commonly used assessments methods of depression; PHQ-9, BDI, and the HDRS (lowest PHQ-9 vs HDRS: r = .728) [72 Table 3], and CES-D and BDI have also been shown to be highly correlated (r = .839, p < .01) [73]. Patient-based outcome measures such as PHQ-9 and BDI have the benefit of being conducted outside the clinic, target very specific symptoms, exclude clinician bias, and facilitate the doctor-patient communication, while it has some drawbacks such as a biased response depending on the recipient, and a lack of meaningful interpretation of the changes to the outcome value [74].…”
Section: Mood Assessmentmentioning
confidence: 99%